Intermetallic nano-catalyst for efficient hydrogen evolution and preparation method of intermetallic nano-catalyst
By preparing RuCo@NC composite materials, using porous carbon to coat intermetallic nanoparticles, the problem of insufficient performance of non-precious metal catalysts in electrocatalytic water decomposition is solved, and high-efficiency and stable electrocatalytic performance and low-cost hydrogen precipitation reaction are achieved. .
Patent Information
- Application Number
- CN202411257776.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-09
AI Technical Summary
In the prior art, non-precious metal catalysts have insufficient catalytic performance and poor stability during electrocatalytic water decomposition, making it difficult to replace precious metal catalysts, especially in high temperature environments, the structure of metal-organic frame materials is easily destroyed, which limits their hydrogen precipitation reaction. performance in.
By preparing Ru@ZIF-8 precursor and introducing cobalt salt and zinc salt on it, forming a Co-ZIF-8/Ru@ZIF-8 core-shell structure, further constructing RuCo@NC composite materials, using porous carbon packages Cover the intermetallic nanoparticles to avoid agglomeration of metal atoms, improve conductivity and exposure of active sites.
It achieves efficient and stable electrocatalytic performance, reduces reaction energy consumption, simplifies the preparation process, is low in cost, is suitable for industrial production, and expands to the preparation of other transition metal composite materials.
Smart Images

Figure CN119121293A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to an intermetallic nanocatalyst for efficient hydrogen evolution and a preparation method thereof. Background Art
[0002] As a clean and sustainable new energy source, hydrogen energy is expected to become one of the means to solve the problems of excessive carbon dioxide emissions and shortage of fossil energy. At present, countries around the world are actively developing hydrogen energy, especially Japan, which has taken the lead and made the development of hydrogen energy a national policy. With the increasing pressure of current environmental pollution, the society's demand for large-scale use of clean new energy is more urgent. One of the important ways to develop high-purity hydrogen is to produce hydrogen by electrocatalytic water decomposition, but the efficiency of hydrogen evolution reaction (HER) still needs to be improved. Therefore, more stringent requirements are put forward for the cost, catalytic activity and catalytic stability of hydrogen evolution catalytic materials. At present, carbon-supported platinum (Pt / C) catalyst is the most ideal catalyst material currently used in commercialization. However, the rare and expensive platinum greatly limits the widespread commercialization of hydrogen evolution by electrolysis of water.
[0003] In the past decade, non-precious metal catalysts have been widely and deeply developed due to their excellent performance and are regarded as the most likely alternative to platinum-based catalysts. However, in the harsh real-world environment, the catalytic performance of transition metal electrocatalysts is still far from meeting the requirements, and their stability has become the biggest bottleneck. Therefore, people urgently need to develop efficient, stable, low-cost, and abundant electrocatalysts to replace precious metal catalysts. Water electrolysis catalysts that can catalyze hydrogen evolution reactions can achieve more efficient full water decomposition reactions. They can greatly reduce the cost of electrode preparation and hydrogen production, simplify the production process, and therefore have broader application prospects. However, how to design and prepare highly active, stable, cheap and easily available hydrogen evolution catalytic materials has become a difficult problem in the current research in this field. Researchers have developed many non-precious metal hydrogen evolution catalytic materials to reduce the overpotential of the system, reduce energy consumption, and improve the catalytic stability of the electrode.
[0004] Intermetallic compounds are a typical hydrogen evolution catalyst, and their adsorption of hydrogen is generally very strong, which limits their performance in hydrogen evolution. The traditional method is to dope intermetallic compounds with anions or cations to optimize their hydrogen evolution performance, but it is still difficult to control the doping amount and dispersion of the doping material. Metal-organic framework materials (MOFs) have poor electrical conductivity and are not ideal for direct electrocatalytic hydrogen evolution. Therefore, they are usually used as precursors to synthesize various transition metal catalysts. However, the high temperature process easily destroys the structure of MOFs and causes the agglomeration of active sites. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a metal nanocatalyst for efficient hydrogen evolution and a preparation method thereof. The technical problem to be solved by the present invention is achieved by the following technical solution:
[0006] The present invention provides a method for preparing an intermetallic nanocatalyst for efficient hydrogen evolution, comprising:
[0007] S1: Preparation of Ru@ZIF-8 precursor;
[0008] S2: using the Ru@ZIF-8 precursor as a crystal core structure, introducing a cobalt salt, a zinc salt and dimethylimidazole in a suitable proportion, and epitaxially growing Co-ZIF-8 on the crystal core structure to form a Co-ZIF-8 / Ru@ZIF-8 precursor with a core-shell structure;
[0009] S3: Using the Co-ZIF-8 / Ru@ZIF-8 precursor, in situ constructing the intermetallic nanocatalyst RuCo@NC.
[0010] In one embodiment of the present invention, the S1 includes:
[0011] S1.1: Using the coordination effect of Zn ions and dimethylimidazole, a ZIF-8 precursor with a dodecahedral structure of transition metal is formed;
[0012] S1.2: Adsorption of Ru using the porous structure of the precursor ZIF-8 3+ , prepare Ru@ZIF-8 precursor.
[0013] In one embodiment of the present invention, the S1.1 includes:
[0014] Weigh an appropriate amount of Zn(NO3)2·6H2O and dissolve it in methanol solution to form solution A;
[0015] Weigh an appropriate amount of dimethylimidazole and dissolve it in the methanol solution to form solution B;
[0016] The solution A is added dropwise to the solution B, and stirred thoroughly at room temperature to obtain a first suspension;
[0017] The obtained first suspension is centrifuged and washed with methanol for multiple times, and then the washed first product is placed in a drying oven for constant temperature drying to obtain the ZIF-8 precursor.
[0018] In one embodiment of the present invention, the mass ratio of the Zn(NO3)2·6H2O to the dimethylimidazole is (1:2) to (1:3).
[0019] In one embodiment of the present invention, the S1.2 includes:
[0020] Weigh an appropriate amount of RuClз·xH2O and dissolve it in deionized water to form solution C;
[0021] Weigh an appropriate amount of the ZIF-8 precursor, dissolve it in a deionized water solution, and disperse it evenly by ultrasonication to form a D solution;
[0022] Add the C solution dropwise into the D solution and stir thoroughly at room temperature to obtain a second suspension;
[0023] The obtained second suspension was centrifuged and washed several times with a mixed solution of ethanol and deionized water, and then the washed second product was placed in a drying oven for constant temperature drying to obtain a Ru@ZIF-8 precursor.
[0024] In one embodiment of the present invention, the mass ratio of the RuClз·xH2O to the ZIF-8 precursor is (1:50) to (1:25).
[0025] In one embodiment of the present invention, the S2 includes:
[0026] Weigh an appropriate amount of the Ru@ZIF-8 precursor and dissolve it in a methanol solution to form a solution E;
[0027] Weigh appropriate amounts of Zn(NO3)2·6H2O and Co(NO3)2·6H2O and dissolve them in methanol solution to form solution F;
[0028] The F solution is dropped into the E solution, and the mixture is stirred at room temperature, and then an appropriate amount of a methanol solution of dimethylimidazole is added dropwise, and the mixture is stirred at room temperature to obtain a third suspension;
[0029] The obtained third suspension was centrifuged and washed with ethanol for multiple times. Finally, the washed third product was placed in a drying oven for constant temperature drying to obtain a Co-ZIF-8 / Ru@ZIF-8 precursor.
[0030] In one embodiment of the present invention, the mass ratio of the Zn(NO3)2·6H2O, the Co(NO3)2·6H2O and the dimethylimidazole is (4:1:1.4) to (2:1:0.8).
[0031] In one embodiment of the present invention, S3 includes:
[0032] The freeze-dried Co-ZIF-8 / Ru@ZIF-8 precursor was placed in a horizontal tube furnace, heated to 900-1000°C at a rate of 5-10°C / min under an inert atmosphere and kept warm for 3-6 hours to obtain a RuCo@NC composite material.
[0033] Another aspect of the present invention provides an intermetallic nanocatalyst for efficient hydrogen evolution, which is prepared using the preparation method described in any one of the above embodiments.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The present invention provides a metal intermetallic nanocatalyst RuCo@NC for efficient hydrogen evolution and a preparation method thereof. The RuCo@NC is a composite material. In the prepared RuCo@NC composite material, transition metal cobalt quantum dots are evenly dispersed and active sites are fully exposed. The RuCo@NC composite material has a core-shell structure and a large specific surface area, so that its application in electrocatalysis can maintain high catalytic activity, excellent stability and excellent conductivity. The preparation raw materials only involve zinc nitrate hexahydrate, cobalt nitrate hexahydrate, dimethylimidazole, and methanol, ethanol and other commonly used reagents and trace precious metals, low cost, high product purity, simple preparation process, easy industrial production, and the preparation process of the present invention can also be extended to the preparation of other transition metal composite electrocatalysts.
[0036] 2. The present invention uses the metal-organic framework material (MOFs) precursor Ru@ZIF-8, introduces a very small amount of precious metal Ru, and regulates the spatial distance between metal sites by parameters such as reaction time, reaction temperature, and raw material ratio, so as to effectively avoid the agglomeration of metal atoms at high temperatures during the thermal cracking process, and prepare an ultrafine metal nanocomposite catalyst supported on porous carbon.
[0037] 3. The preparation method of the present invention can prepare a composite material with a unique three-dimensional core-shell structure and a high specific surface area, effectively inhibiting the agglomeration of metal nanoparticles and fully exposing the active sites; in situ cracking under a high temperature environment obtains porous carbon-coated metal nanoparticles, improves the conductivity of the composite material, and is beneficial to accelerate the transmission of protons and ions during the reaction; innovatively proposes to dope a very small amount of precious metal Ru on the basis of the transition metal-based composite material, which greatly improves the reaction activity and reduces the reaction energy barrier, so that the composite material shows excellent electrocatalytic properties when used as a catalyst for hydrogen evolution reaction.
[0038] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a schematic flow chart of a method for preparing an intermetallic nanocatalyst for efficient hydrogen evolution provided by an embodiment of the present invention;
[0040] Figure 2 is a scanning electron microscope image (SEM) of the RuCo@NC composite material prepared in Example 2 of the present invention;
[0041] Figure 3 is a transmission electron microscope image (TEM) of the RuCo@NC composite material prepared in Example 2 of the present invention;
[0042] Figure 4 is an X-ray diffraction spectrum analysis diagram (XRD) of the RuCo@NC composite material prepared in Example 2 of the present invention;
[0043] Figure 5 This is a linear scanning voltammogram of the HER of the RuCo@NC composite material prepared in Example 2 of the present invention in a 1.0 mol / L potassium hydroxide electrolyte at a scanning rate of 5 mV / s. DETAILED DESCRIPTION
[0044] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of an intermetallic nanocatalyst for efficient hydrogen evolution and a preparation method thereof proposed in accordance with the present invention in conjunction with the accompanying drawings and specific implementation methods.
[0045] The above and other technical contents, features and effects of the present invention are clearly presented in the following detailed description of the specific implementation modes in conjunction with the accompanying drawings. Through the description of the specific implementation modes, the technical means and effects adopted by the present invention to achieve the predetermined purpose can be more deeply and specifically understood. However, the attached drawings are only for reference and explanation purposes and are not used to limit the technical solutions of the present invention.
[0046] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants are intended to cover non-exclusive inclusion, so that an article or device including a series of elements includes not only those elements, but also other elements that are not explicitly listed. In the absence of more restrictions, the elements defined by the statement "including one..." do not exclude the existence of other identical elements in the article or device including the elements.
[0047] Embodiment 1
[0048] See also Figure 1 , Figure 1 1 is a schematic flow chart of a method for preparing a metal nanocatalyst for efficient hydrogen evolution provided by an embodiment of the present invention. The preparation method specifically comprises the following steps:
[0049] S1: Preparation of Ru@ZIF-8 precursor.
[0050] Step S1 of this embodiment includes:
[0051] S1.1: Using the coordination effect of Zn ions and dimethylimidazole, a ZIF-8 precursor with a transition metal dodecahedral structure is formed.
[0052] Weigh an appropriate amount of Zn(NO3)2·6H2O and dissolve it in a methanol solution to form a solution A; weigh an appropriate amount of dimethylimidazole and dissolve it in a methanol solution to form a solution B; drop the solution A into the solution B, stir it thoroughly at room temperature, and obtain a first suspension; centrifuge the obtained first suspension and wash it with methanol for multiple times, then place the washed first product in a drying oven for constant temperature drying to obtain the ZIF-8 precursor. The mass ratio of the Zn(NO3)2·6H2O to the dimethylimidazole is (1:2) to (1:3), preferably 1:2.4.
[0053] Specifically, 800-1000 mg of Zn(NO3)2·6H2O was weighed and dissolved in 25 mL of methanol solution, which was recorded as solution A; 2-3 g of dimethylimidazole was weighed and dissolved in 25 mL of methanol solution, which was recorded as solution B; solution A was slowly dripped into solution B, and stirred at room temperature for 4-8 hours to obtain a suspension. The obtained suspension was centrifuged and washed with methanol for 3-4 times. Finally, the product was placed in a drying oven at 60-100°C and dried at a constant temperature for 8 hours to obtain a ZIF-8 precursor.
[0054] S1.2: Adsorption of Ru using the porous structure of the precursor ZIF-8 3+ , prepare Ru@ZIF-8 precursor.
[0055] Weigh an appropriate amount of RuClз·xH2O and dissolve it in a deionized water solution to form a C solution; weigh an appropriate amount of the ZIF-8 precursor and dissolve it in a deionized water solution and disperse it evenly by ultrasonication to form a D solution; drop the C solution into the D solution and stir it thoroughly at room temperature to obtain a second suspension; centrifuge the obtained second suspension and wash it several times with a mixed solution of ethanol and deionized water, then place the washed second product in a drying oven and dry it at a constant temperature to obtain a Ru@ZIF-8 precursor. The mass ratio of the RuClз·xH2O to the ZIF-8 precursor is (1:50) to (1:25).
[0056] Specifically, 1-4 mg of RuClз·xH2O (hydrated ruthenium trichloride) was weighed and dissolved in 5 mL of deionized water solution, recorded as solution C, 80-110 mg of ZIF-8 was weighed and dissolved in 5 mL of deionized water solution and ultrasonically dispersed uniformly, recorded as solution D, solution C was slowly dripped into solution D, stirred at room temperature for 40-50 min, and a second suspension was obtained. The obtained second suspension was centrifuged and washed 3-4 times with a mixed solution of ethanol and deionized water. Finally, the washed second product was placed in a drying oven at 60-100 ° C and dried at a constant temperature for 6-10 hours to obtain the precursor Ru@ZIF-8.
[0057] It should be noted that the morphology, phase composition, and dodecahedron size of Ru@ZIF-8 can be controlled by adjusting the amounts of RuClз·xH2O and ZIF-8 precursor and adding surfactants.
[0058] S2: using the Ru@ZIF-8 precursor as a crystal core structure, introducing cobalt salt, zinc salt and dimethylimidazole in appropriate proportions, and epitaxially growing Co-ZIF-8 on the crystal core structure to form a Co-ZIF-8 / Ru@ZIF-8 precursor with a core-shell structure.
[0059] Weigh an appropriate amount of the Ru@ZIF-8 precursor and dissolve it in a methanol solution to form an E solution; weigh an appropriate amount of Zn(NO3)2·6H2O and Co(NO3)2·6H2O and dissolve them in a methanol solution to form an F solution; drop the F solution into the E solution, stir it thoroughly at room temperature, then drop an appropriate amount of a methanol solution of dimethylimidazole, stir it thoroughly at room temperature, and obtain a third suspension; centrifuge the obtained third suspension and wash it with ethanol for multiple times, and finally place the washed third product in a drying oven to dry at a constant temperature to obtain a Co-ZIF-8 / Ru@ZIF-8 precursor. The mass ratio of the Zn(NO3)2·6H2O, the Co(NO3)2·6H2O and the dimethylimidazole is (4:1:1.4) to (2:1:0.8).
[0060] Specifically, 30-60 mg of Ru@ZIF-8 was weighed and dissolved in 10 mL of methanol solution, recorded as E solution, 230-300 mg of Zn(NO3)2·6H2O and 30-60 mg of Co(NO3)2·6H2O were weighed and dissolved in 10 mL of methanol solution, recorded as F solution, and F solution was slowly dripped into E solution and stirred at room temperature for 20-40 min. 70-100 mg of dimethylimidazole was dissolved in 10 mL of methanol solution, stirred at room temperature for 20-30 h, and then slowly dripped into the mixed solution of F solution and E solution. The obtained third suspension was centrifuged and washed with ethanol 3-4 times. Finally, the washed third product was placed in a drying oven at 60-100 ° C and dried at a constant temperature for 6-10 h to obtain Co-ZIF-8 / Ru@ZIF-8 precursor.
[0061] It should be noted that the morphology, phase composition, core-shell thickness, etc. of the Co-ZIF-8 / Ru@ZIF-8 precursor can be controlled by adjusting the ratio of zinc salt (Zn(NO3)2·6H2O) and cobalt salt (Co(NO3)2·6H2O), the concentration of reactants such as dimethylimidazole, and the addition of surfactants.
[0062] S3: Using the Co-ZIF-8 / Ru@ZIF-8 precursor, in situ constructing the intermetallic nanocatalyst RuCo@NC.
[0063] The freeze-dried Co-ZIF-8 / Ru@ZIF-8 precursor is placed in a horizontal tube furnace, heated to 900-1000°C at a rate of 5-10°C / min under an inert atmosphere or a reducing atmosphere, and kept warm at this temperature for 3-6 hours to obtain a RuCo@NC composite material. In this embodiment, the reducing atmosphere is a hydrogen-argon mixture. The cobalt and ruthenium in the Co-ZIF-8 / Ru@ZIF-8 precursor will undergo an alloying reaction in a reducing atmosphere and at a certain temperature. In this process, the Co-ZIF-8 / Ru@ZIF-8 precursor retains the carbon skeleton, while the metal ruthenium and cobalt undergo an alloying reaction under high-temperature reducing conditions to form a ruthenium-cobalt nanoalloy. By changing the experimental conditions and process parameters such as the carrier gas atmosphere, gas flow rate, reaction temperature and time, a carbon-coated intermetallic nanocomposite catalyst is constructed in situ. The effects of different calcination atmospheres, gas flow rates, calcination temperatures, calcination times, precursor morphology, composition and other factors on the morphology, intermetallic components, pore size distribution, N doping amount, crystal defects, etc. of RuCo@NC were studied. In-situ pyrolysis at high temperatures yielded porous carbon-coated intermetallic nanoparticles, which improved the conductivity of the composite material and helped accelerate the transport of protons and ions during the reaction.
[0064] The RuCo@NC composite material prepared by the present invention has a unique core-shell structure, a large specific surface area, and uniformly dispersed transition metal ruthenium-based quantum dots, so that the active sites of the catalyst are fully exposed; in addition, the RuCo@NC composite material has abundant N doping, which can achieve better synergy, so that the RuCo@NC composite material, when used as a functional electrocatalyst for hydrogen evolution reaction, shows excellent electrocatalytic properties (HER (hydrogen evolution reaction) overpotential: η10mA cm in 1.0Mol / L KOH solution). -2 =133mV), the RuCo@NC composite material prepared by the present invention not only has strong conductivity, multiple active sites, and good electrocatalytic performance, but also has low raw material cost, simple process, low reaction energy consumption, and can be prepared on a large scale. It is an efficient and economical preparation method for a new type of water electrolysis catalyst.
[0065] When the RuCo@NC composite material prepared by the present invention is used as a water electrolysis catalyst, the specific steps are as follows: the prepared RuCo@NC composite material is loaded on a glassy carbon electrode as a working electrode, a saturated calomel electrode is used as a reference electrode, and a carbon rod is used as a counter electrode. The HER electrochemical performance thereof is tested in a 1.0Mol / L KOH solution at room temperature and pressure.
[0066] The invention provides an intermetallic nanocatalyst RuCo@NC for efficient hydrogen evolution and a preparation method thereof. The RuCo@NC is a composite material. In the prepared RuCo@NC composite material, transition metal cobalt quantum dots are evenly dispersed and active sites are fully exposed. The RuCo@NC composite material has a core-shell structure and a large specific surface area, so that its application in electrocatalysis can maintain high catalytic activity, excellent stability and excellent conductivity. The preparation raw materials only involve zinc nitrate hexahydrate, cobalt nitrate hexahydrate, dimethylimidazole, methanol, ethanol and other commonly used reagents and trace precious metals, the cost is low, the product purity is high, the preparation process is simple, and it is easy to industrialize production. Moreover, the preparation process of the invention can also be extended to the preparation of other transition metal composite material electrocatalysts.
[0067] Embodiment 2
[0068] Based on Example 1, this example provides a core-shell metal organic framework compound (MOFs) derived metal nanocatalyst for efficient hydrogen evolution and a preparation method thereof, wherein the chemical expression thereof is RuCo@NC. The preparation method specifically comprises the following steps:
[0069] Step 1: Preparation of MOFs material Ru@ZIF-8 anchoring precious metal ions.
[0070] The coordination of Zn ions and dimethylimidazole is used to form a transition metal dodecahedral structure (ZIF-8). Specifically, 961.4 mg of Zn(NO3)2·6H2O was weighed and dissolved in 25 mL of methanol solution as solution A, and 2.357 g of dimethylimidazole was weighed and dissolved in 25 mL of methanol solution as solution B. Solution A was slowly dripped into solution B and stirred at room temperature for 6 hours. The first suspension obtained was centrifuged and washed with methanol 3-4 times. Finally, the washed first product was placed in a drying oven at 80°C and dried at a constant temperature for 8 hours to obtain a ZIF-8 precursor.
[0071] Subsequently, the porous structure of the ZIF-8 precursor was used to adsorb Ru3+ to prepare Ru@ZIF-8. Specifically, 2 mg of RuClз·xH2O was weighed and dissolved in 5 mL of deionized water solution, recorded as solution C, 100 mg of ZIF-8 precursor was weighed and dissolved in 5 mL of deionized water solution and ultrasonically dispersed uniformly, recorded as solution D, solution C was slowly dripped into solution D, stirred at room temperature for 30 minutes, and a second suspension was obtained. The obtained second suspension was centrifuged and washed 3-4 times with a mixed solution of ethanol and deionized water. Finally, the washed second product was placed in a drying oven at 80°C and dried at a constant temperature for 8 hours to obtain a Ru@ZIF-8 precursor.
[0072] Step 2: Use Ru@ZIF-8 precursor to in situ construct the core-shell metal-based MOFs precursor Co-ZIF-8 / Ru@ZIF-8.
[0073] Using Ru@ZIF-8 as the crystal core structure, Co-ZIF-8 was epitaxially grown on the crystal core by introducing appropriate proportions of cobalt salt, zinc salt and dimethylimidazole to form a metal-based MOFs precursor Co-ZIF-8 / Ru@ZIF-8 with a core-shell structure. Specifically, 50 mg of Ru@ZIF-8 precursor was weighed and dissolved in 10 mL of methanol solution, recorded as E solution, 236.8 mg of Zn(NO3)2·6H2O and 59.2 mg of Co(NO3)2·6H2O were weighed and dissolved in 10 mL of methanol solution, recorded as F solution, and F solution was slowly dripped into E solution and stirred at room temperature for 30 minutes. Subsequently, 82 mg of dimethylimidazole was dissolved in 10 mL of methanol solution, stirred at room temperature for 24 hours, and then slowly dripped into the mixed solution of F solution and E solution. The obtained third suspension was centrifuged and washed with ethanol 3-4 times. Finally, the cleaned third product was placed in a drying oven at 80°C and dried at a constant temperature for 8 hours to obtain the Co-ZIF-8 / Ru@ZIF-8 precursor.
[0074] Step 3: Use Co-ZIF-8 / Ru@ZIF-8 precursor to in situ construct the intermetallic nanocatalyst RuCo@NC.
[0075] The freeze-dried precursor is placed in a horizontal tube furnace, heated to 950°C at a rate of 5°C / min in an inert atmosphere or a reducing atmosphere, and kept at this temperature for 6 hours to obtain a RuCo@NC composite material.
[0076] See also Figure 2 , Figure 2 is a scanning electron microscope (SEM) image of the RuCo@NC composite material prepared in Example 2 of the present invention. Figure 2 It can be seen that the RuCo@NC composite material after pyrolysis can still basically maintain the structure of a regular dodecahedron, indicating that it retains the framework structure of the precursor well;
[0077] See also Figure 3 , Figure 3 FIG. 1 is a transmission electron microscope image (TEM) of the RuCo@NC composite material prepared in Example 2 of the present invention. Figure 3 It can be seen that the RuCo@NC sample still maintains a porous regular dodecahedron core-shell structure. It can also be observed that the RuCo nanometal particles covering the middle layer of the core-shell structure do not agglomerate and are evenly distributed in the middle layer of the core-shell material.
[0078] See also Figure 4 , Figure 4 This is the X-ray diffraction spectrum analysis diagram (XRD) of the RuCo@NC composite material prepared in Example 2 of the present invention. Figure 4 It can be seen that the characteristic peaks of Co are observed at 44.45° and 69.9° in the XRD diffraction peaks of the RuCo@NC sample. Since the characteristic peak of Ru is located at 44.0° and has a high intensity, it overlaps with the characteristic peak of Co, so it is difficult to directly observe the peak of Ru in the XRD image.
[0079] See also Figure 5 , Figure 5 The HER linear scanning voltammetry curve of the RuCo@NC composite material prepared in Example 2 of the present invention in a 1.0 mol / L potassium hydroxide electrolyte at a scanning rate of 5 mV / s is shown in FIG. -2 When the overpotential of RuCo@NC is 154mV, the overpotential of RuCo@NC is 154mV. In practical applications, the ultimate goal of electrocatalytic water decomposition to produce hydrogen is to reduce costs and increase efficiency. This embodiment uses ultra-low amounts of precious metal Ru to help improve the intrinsic activity of low-cost transition metal Co, thereby significantly reducing costs and effectively improving the catalytic performance of RuCo@NC electrocatalysis.
[0080] Embodiment 3
[0081] On the basis of the above embodiment, this embodiment provides another preparation method and application of an intermetallic nanocatalyst RuCo@NC (denoted as RuCo@NC-1) for efficient hydrogen evolution. The specific preparation method is as follows:
[0082] Step 1: Preparation of MOFs material Ru@ZIF-8 anchoring precious metal ions.
[0083] The coordination of Zn ions and dimethylimidazole is used to form a transition metal dodecahedral structure (ZIF-8): 961.4 mg of Zn(NO3)2·6H2O is dissolved in 25 mL of methanol solution as solution A, 2.357 g of dimethylimidazole is dissolved in 25 mL of methanol solution as solution B, solution A is slowly dripped into solution B, and stirred at room temperature for 6 hours. The first suspension obtained is centrifuged and washed with methanol 3-4 times. Finally, the washed first product is placed in a drying oven at 80°C and dried at a constant temperature for 8 hours to obtain a ZIF-8 precursor.
[0084] Subsequently, the porous structure of the ZIF-8 precursor was used to adsorb Ru3+ to prepare Ru@ZIF-8. Specifically, 2 mg of RuClз·xH2O was weighed and dissolved in 5 mL of deionized water solution, recorded as solution C, 100 mg of ZIF-8 precursor was weighed and dissolved in 5 mL of deionized water solution and ultrasonically dispersed uniformly, recorded as solution D, solution C was slowly dripped into solution D, stirred at room temperature for 30 minutes, and a second suspension was obtained. The obtained second suspension was centrifuged and washed 3-4 times with a mixed solution of ethanol and deionized water. Finally, the washed second product was placed in a drying oven at 80°C and dried at a constant temperature for 8 hours to obtain a Ru@ZIF-8 precursor.
[0085] Step 2: Use Ru@ZIF-8 precursor to in situ construct the core-shell metal-based MOFs precursor Co-ZIF-8 / Ru@ZIF-8.
[0086] Using Ru@ZIF-8 as the crystal core structure, Co-ZIF-8 was epitaxially grown on the crystal core by introducing appropriate proportions of cobalt salt, zinc salt and dimethylimidazole to form a metal-based MOFs precursor Co-ZIF-8 / Ru@ZIF-8 with a core-shell structure. Specifically, 50 mg of Ru@ZIF-8 precursor was weighed and dissolved in 10 mL of methanol solution, recorded as E solution, 197.3 mg of Zn(NO3)2·6H2O and 98.67 mg of Co(NO3)2·6H2O were weighed and dissolved in 10 mL of methanol solution, recorded as F solution, and F solution was slowly dripped into E solution and stirred at room temperature for 30 minutes. Subsequently, 82 mg of dimethylimidazole was dissolved in 10 mL of methanol solution, stirred at room temperature for 24 hours, and then slowly dripped into the mixed solution of F solution and E solution. The obtained third suspension was centrifuged and washed with ethanol 3-4 times. Finally, the cleaned third product was placed in a drying oven at 80°C and dried at a constant temperature for 8 hours to obtain the Co-ZIF-8 / Ru@ZIF-8 precursor.
[0087] Step 3: Use Co-ZIF-8 / Ru@ZIF-8 precursor to in situ construct the intermetallic nanocatalyst RuCo@NC.
[0088] The freeze-dried precursor is placed in a horizontal tube furnace, heated to 950°C at a rate of 5°C / min in an inert atmosphere or a reducing atmosphere, and kept at this temperature for 6 hours to obtain a RuCo@NC composite material.
[0089] Embodiment 4
[0090] On the basis of the above embodiment, this embodiment provides another preparation method and application of an intermetallic nanocatalyst RuCo@NC (denoted as RuCo@NC-2) for efficient hydrogen evolution. The specific preparation method is as follows:
[0091] Step 1: Preparation of MOFs material Ru@ZIF-8 anchoring precious metal ions.
[0092] The coordination of Zn ions and dimethylimidazole is used to form a transition metal dodecahedral structure (ZIF-8). Specifically, 961.4 mg of Zn(NO3)2·6H2O was weighed and dissolved in 25 mL of methanol solution as solution A, and 2.357 g of dimethylimidazole was weighed and dissolved in 25 mL of methanol solution as solution B. Solution A was slowly dripped into solution B and stirred at room temperature for 6 hours. The first suspension obtained was centrifuged and washed with methanol 3-4 times. Finally, the washed first product was placed in a drying oven at 80°C and dried at a constant temperature for 8 hours to obtain a ZIF-8 precursor.
[0093] Subsequently, the porous structure of the ZIF-8 precursor was used to adsorb Ru3+ to prepare Ru@ZIF-8. Weigh 4 mg of RuClз·xH2O and dissolve it in 5 mL of deionized water solution as solution C, weigh 100 mg of ZIF-8 precursor and dissolve it in 5 mL of deionized water solution as solution D and ultrasonically disperse it evenly as solution D. Slowly drip solution C into solution D and stir at room temperature for 30 minutes to obtain a second suspension. The obtained second suspension was centrifuged and washed 3-4 times with a mixed solution of ethanol and deionized water. Finally, the washed second product was placed in a drying oven at 80°C and dried at a constant temperature for 8 hours to obtain a Ru@ZIF-8 precursor.
[0094] Step 2: Use Ru@ZIF-8 precursor to in situ construct the core-shell metal-based MOFs precursor Co-ZIF-8 / Ru@ZIF-8.
[0095] Using Ru@ZIF-8 as the crystal core structure, Co-ZIF-8 was epitaxially grown on the crystal core by introducing appropriate proportions of cobalt salt, zinc salt and dimethylimidazole to form a metal-based MOFs precursor Co-ZIF-8 / Ru@ZIF-8 with a core-shell structure. Specifically, 50 mg of Ru@ZIF-8 precursor was weighed and dissolved in 10 mL of methanol solution, recorded as E solution, 236.8 mg of Zn(NO3)2·6H2O and 59.2 mg of Co(NO3)2·6H2O were weighed and dissolved in 10 mL of methanol solution, recorded as F solution, and F solution was slowly dripped into E solution and stirred at room temperature for 30 minutes. Subsequently, 82 mg of dimethylimidazole was dissolved in 10 mL of methanol solution, stirred at room temperature for 24 hours, and then slowly dripped into the mixed solution of F solution and E solution. The obtained third suspension was centrifuged and washed with ethanol 3-4 times. Finally, the cleaned third product was placed in a drying oven at 80°C and dried at a constant temperature for 8 hours to obtain the Co-ZIF-8 / Ru@ZIF-8 precursor.
[0096] Step 3: Use Co-ZIF-8 / Ru@ZIF-8 precursor to in situ construct the intermetallic nanocatalyst RuCo@NC.
[0097] The freeze-dried precursor is placed in a horizontal tube furnace, heated to 950°C at a rate of 5°C / min in an inert atmosphere or a reducing atmosphere, and kept at this temperature for 6 hours to obtain a RuCo@NC composite material.
[0098] Embodiment 5
[0099] On the basis of the above embodiment, this embodiment provides another preparation method and application of an intermetallic nanocatalyst RuCo@NC (denoted as RuCo@NC-3) for efficient hydrogen evolution. The specific preparation method is as follows:
[0100] Step 1: Preparation of MOFs material Ru@ZIF-8 anchoring precious metal ions.
[0101] The coordination of Zn ions and dimethylimidazole is used to form a transition metal dodecahedral structure (ZIF-8): 961.4 mg of Zn(NO3)2·6H2O is dissolved in 25 mL of methanol solution as solution A, 2.357 g of dimethylimidazole is dissolved in 25 mL of methanol solution as solution B, solution A is slowly dripped into solution B, and stirred at room temperature for 6 hours. The first suspension obtained is centrifuged and washed with methanol 3-4 times. Finally, the washed first product is placed in a drying oven at 80°C and dried at a constant temperature for 8 hours to obtain a ZIF-8 precursor.
[0102] Subsequently, the porous structure of the ZIF-8 precursor was used to adsorb Ru3+ to prepare Ru@ZIF-8. Weigh 4 mg of RuClз·xH2O and dissolve it in 5 mL of deionized water solution, record it as solution C, weigh 100 mg of ZIF-8 precursor and dissolve it in 5 mL of deionized water solution and disperse it evenly by ultrasonication, record it as solution D, slowly drip solution C into solution D, stir at room temperature for 30 minutes, and obtain the second suspension. The obtained second suspension was centrifuged and washed 3-4 times with a mixed solution of ethanol and deionized water. Finally, the washed second product was placed in a drying oven at 80°C and dried at a constant temperature for 8 hours to obtain the Ru@ZIF-8 precursor.
[0103] Step 2: Use Ru@ZIF-8 precursor to in situ construct the core-shell metal-based MOFs precursor Co-ZIF-8 / Ru@ZIF-8.
[0104] Using Ru@ZIF-8 as the crystal core structure, Co-ZIF-8 was epitaxially grown on the crystal core by introducing appropriate proportions of cobalt salt, zinc salt and dimethylimidazole to form a metal-based MOFs precursor Co-ZIF-8 / Ru@ZIF-8 with a core-shell structure. Specifically, 50 mg of Ru@ZIF-8 precursor was weighed and dissolved in 10 mL of methanol solution, recorded as E solution, 197.3 mg of Zn(NO3)2·6H2O and 98.67 mg of Co(NO3)2·6H2O were weighed and dissolved in 10 mL of methanol solution, recorded as F solution, and F solution was slowly dripped into E solution and stirred at room temperature for 30 minutes. Subsequently, 82 mg of dimethylimidazole was dissolved in 10 mL of methanol solution, stirred at room temperature for 24 hours, and then slowly dripped into the mixed solution of F solution and E solution. The obtained third suspension was centrifuged and washed with ethanol 3-4 times. Finally, the cleaned third product was placed in a drying oven at 80°C and dried at a constant temperature for 8 hours to obtain the Co-ZIF-8 / Ru@ZIF-8 precursor.
[0105] Step 3: Use Co-ZIF-8 / Ru@ZIF-8 precursor to in situ construct the intermetallic nanocatalyst RuCo@NC.
[0106] The freeze-dried precursor is placed in a horizontal tube furnace, heated to 950°C at a rate of 5°C / min in an inert atmosphere or a reducing atmosphere, and kept at this temperature for 6 hours to obtain a RuCo@NC composite material.
[0107] Another aspect of the present invention provides an intermetallic nanocatalyst for efficient hydrogen evolution, which is prepared using the preparation method described in any one of the above embodiments.
[0108] In summary, the present invention uses metal-organic framework (MOFs) precursor Ru@ZIF-8, introduces a very small amount of precious metal Ru, regulates the spatial distance between metal sites by parameters such as reaction time, reaction temperature, and raw material ratio, effectively avoids the agglomeration of metal atoms at high temperature during the thermal cracking process, and prepares an ultrafine metal intermetallic nanocomposite catalyst loaded on porous carbon. The preparation method of the present invention can prepare a composite material with a unique three-dimensional core-shell structure and a high specific surface area, effectively inhibits the agglomeration of metal nanoparticles, and fully exposes the active sites; in-situ cracking under a high temperature environment obtains porous carbon-coated metal intermetallic nanoparticles, improves the conductivity of the composite material, and is conducive to accelerating the transmission of protons and ions during the reaction process; innovatively proposes to dope a very small amount of precious metal Ru on the basis of a transition metal-based composite material, greatly improves the reaction activity, reduces the reaction energy barrier, and enables the composite material to be used as a catalyst for hydrogen evolution reaction, showing excellent electrocatalytic properties.
[0109] In the several embodiments provided by the present invention, it should be understood that the apparatus and method disclosed by the present invention can be implemented in other ways. For example, the apparatus embodiments described above are only illustrative, for example, the division of the modules is only a logical function division, and there may be other division methods in actual implementation, for example, multiple modules or components can be combined or integrated into another system, or some features can be ignored or not executed.
[0110] In addition, each functional module in each embodiment of the present invention may be integrated into one processing module, or each module may exist physically separately, or two or more modules may be integrated into one module. The above-mentioned integrated module may be implemented in the form of hardware or in the form of hardware plus software functional modules.
[0111] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A method for preparing a metal nanocatalyst for efficient hydrogen evolution, characterized in that: include: S1: Preparation of Ru@ZIF-8 precursor; S2: using the Ru@ZIF-8 precursor as a crystal core structure, introducing a cobalt salt, a zinc salt and dimethylimidazole in a suitable proportion, and epitaxially growing Co-ZIF-8 on the crystal core structure to form a Co-ZIF-8 / Ru@ZIF-8 precursor with a core-shell structure; S3: Using the Co-ZIF-8 / Ru@ZIF-8 precursor, in situ constructing the intermetallic nanocatalyst RuCo@NC.
2. The method for preparing an intermetallic nanocatalyst for efficient hydrogen evolution according to claim 1, characterized in that: The S1 includes: S1.1: Using the coordination effect of Zn ions and dimethylimidazole, a ZIF-8 precursor with a dodecahedral structure of transition metal is formed; S1.2: Adsorption of Ru using the porous structure of the precursor ZIF-8 3+ , prepare Ru@ZIF-8 precursor.
3. The method for preparing an intermetallic nanocatalyst for efficient hydrogen evolution according to claim 2, characterized in that: The S1.1 includes: Weigh an appropriate amount of Zn(NO3)2·6H2O and dissolve it in methanol solution to form solution A; Weigh an appropriate amount of dimethylimidazole and dissolve it in the methanol solution to form solution B; The solution A is added dropwise to the solution B, and stirred thoroughly at room temperature to obtain a first suspension; The obtained first suspension is centrifuged and washed with methanol for multiple times, and then the washed first product is placed in a drying oven for constant temperature drying to obtain the ZIF-8 precursor.
4. The method for preparing an intermetallic nanocatalyst for efficient hydrogen evolution according to claim 3, characterized in that: The mass ratio of the Zn(NO3)2·6H2O to the dimethylimidazole is (1:2) to (1:3).
5. The method for preparing the metal nanocatalyst for efficient hydrogen evolution according to claim 2, characterized in that: The S1.2 includes: Weigh an appropriate amount of RuClз·xH2O and dissolve it in deionized water to form solution C; Weigh an appropriate amount of the ZIF-8 precursor, dissolve it in a deionized water solution, and disperse it evenly by ultrasonication to form a D solution; Add the C solution dropwise into the D solution and stir thoroughly at room temperature to obtain a second suspension; The obtained second suspension was centrifuged and washed several times with a mixed solution of ethanol and deionized water, and then the washed second product was placed in a drying oven for constant temperature drying to obtain a Ru@ZIF-8 precursor.
6. The method for preparing the intermetallic nanocatalyst for efficient hydrogen evolution according to claim 5, characterized in that: The mass ratio of the RuClз·xH2O to the ZIF-8 precursor is (1:50) to (1:25).
7. The method for preparing an intermetallic nanocatalyst for efficient hydrogen evolution according to claim 1, characterized in that: The S2 includes: Weigh an appropriate amount of the Ru@ZIF-8 precursor and dissolve it in a methanol solution to form a solution E; Weigh appropriate amounts of Zn(NO3)2·6H2O and Co(NO3)2·6H2O and dissolve them in methanol solution to form solution F; The F solution is dropped into the E solution, and the mixture is stirred at room temperature, and then an appropriate amount of a methanol solution of dimethylimidazole is added dropwise, and the mixture is stirred at room temperature to obtain a third suspension; The obtained third suspension was centrifuged and washed with ethanol for multiple times. Finally, the washed third product was placed in a drying oven for constant temperature drying to obtain a Co-ZIF-8 / Ru@ZIF-8 precursor.
8. The method for preparing the intermetallic nanocatalyst for efficient hydrogen evolution according to claim 7, characterized in that: The mass ratio of the Zn(NO3)2·6H2O, the Co(NO3)2·6H2O and the dimethylimidazole is (4:1:1.4) to (2:1:0.8).
9. The method for preparing an intermetallic nanocatalyst for efficient hydrogen evolution according to claim 7, characterized in that: The S3 includes: The freeze-dried Co-ZIF-8 / Ru@ZIF-8 precursor is placed in a horizontal tube furnace, heated to 900-1000°C at a rate of 5-10°C / min in an inert atmosphere or a reducing atmosphere and kept warm for 3-6 hours to obtain a RuCo@NC composite material.
10. An intermetallic nanocatalyst for efficient hydrogen evolution, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method and application of bifunctional electrocatalyst of molybdenum disulfide composite material
CN110026210A
Hybrid material of porous cobalt-zinc core-shell metal organic framework compound confinement noble metal nanoparticle, preparation method and application thereof
CN111330639A
Hollow polyhedral structure porous carbon loaded Ru nano particle material and preparation and application thereof
CN113351224A
Sandwich-shaped MxCo9-xSe8-coated NC core-shell nano cubic box electrocatalyst as well as preparation and application thereof
CN115074773A
Preparation method and application of Fe3C-Co-NC composite nanoparticle catalyst
CN115832340A
